Preparation of a china high school teacher in physical education in a network learning format - Wang E.; Yamaletdinova G.A.; Rogaleva L.N.; Yuy I. (Theory and Practice of Physical Culture, 2025)
Objective of the study was to pinpoint the elements of physical education teacher education in Chinese universities in the context of online learning. Methods and structure of the study. The examination of official documents related to online learning, as well as the review of scholarly works on the topic of developing and implementing collaborative Russian-Chinese online educational initiatives, is being conducted. Results and conclusions. The authors reviewed the prospects for the development of Russian-Chinese cooperation in the field of higher education within the framework of the SCO and BRICS Network Universities, clarified the basic concepts of the study, and justified the need to take into account a number of conditions for the creation and effective implementation of a physical education teacher training program for Chinese universities. The authors noted that when developing online educational programs, firstly, it is necessary to conduct a comparative analysis of the quality requirements for teacher training in Russia and China, secondly, it is important to choose key methodological approaches to designing an educational program for the training of physical education teachers, and thirdly, it will require justification and model development. Fourth, the training of physical education teachers in the format of online learning, It is important to pay special attention to the development of organizational and pedagogical conditions for the implementation of the program, within which it is necessary to provide for the development of recommendations for teachers and students.